Head, eye and arm coordination in table tennis - Rodrigues, Sérgio Tosi [UNESP]; Vickers, J. N.; Williams, A. M. (Taylor & Francis Ltd, 2002)
The aim of this study was to determine the role of head, eye and arm movements during the execution of a table tennis forehand stroke. Three-dimensional kinematic analysis of line-of-gaze, arm and ball was used to describe visual and motor behaviour. Skilled and less skilled participants returned the ball to cued right or left target areas under three levels of temporal constraint: pre-, early- and late-cue conditions. In the pre- and early-cue conditions, both high and low skill participants tracked the ball early in flight and kept gaze stable on a location in advance of the ball before ball-bat contact. Skilled participants demonstrated an earlier onset of ball tracking and recorded higher performance accuracy than less skilled counterparts. The manipulation of cue condition showed the limits of adaptation to maintain accuracy on the target. Participants were able to accommodate the constraints imposed by the early-cue condition by using a shorter quiet eye duration, earlier quiet eye offset and reduced arm velocity at contact. In the late-cue condition, modifications to gaze, head and arm movements were not sufficient to preserve accuracy. The findings highlight the functional coupling between perception and action during time-constrained, goal-directed actions.
Keywords: gaze behaviour; interceptive actions; skill; visual perception